Standard STEP process integration and development of computer systems engineering - Stamirowski, Jerzy (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2017)
The integration of information is an essential element of the process automation of design and engineering. Conducted in ISO work led to the development of ISO 10303 STEP harmonizing the information model of the product and creating conditions for the integration of information processes designed and technical preparation of production. The article presents the selected application engineering STEP standard in the Þ eld of technical preparation of production and manufacturing. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)